TRUST IN INFLUENCERS - USING SEVQUAL TO ACHIEVE THE EFFECT OF MANAGING THE HATE MECHANISM - Żywiołek Justyna (International Journal for Quality Research)
The research is aimed at analyzing the phenomenon of hatred that takes place while running profiles on social media by influencers. The study describes the phenomenon of hate used by influencers to build trust among the offenders. The study adopted a literature review to identify research to date. The authors also synthesized the existing literature using the Scopus database in 2019-2022. On this basis, a research survey was developed, which was conducted on a group of 500 influencers between June and December 2021. The survey results fill a gap in the literature at the intersection of work in the digitized world / social media management. In addition, the study also presents the results of qualitative research on the mechanisms of how influencers work with hate. The originality of the research is a literature analysis and maps from the Scopus database. The literature research shows the connections, while the qualitative research shows the scales of the connections. The results of the study indicate that individual factors have a small impact on trust, but the combination of factors has a huge impact. The impact of anti-hate campaigns or the management of hate columns has a significant impact on image building and follower trust. These results are useful for practitioners as they provide new methods for increasing trust in influencers.